BLENDED LEARNING MODEL TO IMPROVE STUDENTS’ LEARNING INDEPENDENCE ON VISUAL PROGRAMMING COURSE - Ratnawati, Dwi (Universitas Teknologi Yogyakarta, 2019)
Abstract- This research aims at finding out the improvement of student learning independence (KBM)through blended learning. The research method employs quasi experimental with design. There are 23students of Information Technology Education that divided into two sample groups, experiment class andcontrol class as the research subject. Experiment class was treated nonequivalent pre-test and post-test andgiven blended learning, while the control group was given conventional learning. The research instrumentconsists of preliminary competence test (KAM) and questionnaire of student learning independence. Thedata are analyzed quantitative descriptive. The research result shows that student learning independencein blended learning class does not improve better than the one which get conventional learning.